The OSI and TCP/ IP Reference Models in the Era of Industry 4.0 - Permana, Eka Ramdan; Wahyu, Fajar Nugraha; Taufik, Handri; T, Thoyyibah (Institut Riset dan Publikasi Indonesia, 2024)
The research aims to evaluate the integration and relevance of the Open Systems Interconnection (OSI) and TCP/IP (Transmission Control Protocol/Internet Protocol) Reference Models in the context of Industry 4.0. This study seeks to analyze the suitability of these models with the complex and dynamic networking environment of the present era and to propose modifications or strategies to enhance their performance and security within the context of Industry 4.0. The research method employed is descriptive research with a literature study design. This descriptive research method with a literature study design will aid in depicting and analyzing the OSI and TCP/IP reference models in the Industry 4.0 era. Primary data sources are derived from scholarly journals, reference books, and other relevant publications. Data analysis is conducted using a qualitative approach, wherein information from various sources will be thoroughly analyzed to identify patterns, trends, and relationships among the studied concepts. The research findings indicate that the difference between the OSI and TCP/IP models lies in their approaches and characteristics in regulating the process of data communication within networks. OSI emphasizes reliability at each layer, while TCP/IP views reliability as an end-to-end issue.